2021
DOI: 10.1029/2021jb022715
|View full text |Cite
|
Sign up to set email alerts
|

Dating Continental Subduction Beneath the Samail Ophiolite: Garnet, Zircon, and Rutile Petrochronology of the As Sifah Eclogites, NE Oman

Abstract: For guidance on citations see FAQs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 122 publications
(445 reference statements)
0
7
0
Order By: Relevance
“…The Semail ophiolite was obducted onto the northeastern margin of the Arabian plate, along with the allochthonous thrust sheets beneath (Coleman, 1981;Glennie et al, 1973Glennie et al, , 1974Searle, 2007). The initial oceanic subduction of Tethyan oceanic crust below the Semail ophiolite occurred at about 96-95 Ma from U-Pb zircon dating of metamorphic sole amphibolites accreted along the base of ophiolite (Rioux et al, 2016) and the ensuing continental margin subduction reached its peak high-pressure metamorphism at about 81-77 Ma (Garber et al, 2021;Warren et al, 2003). The obduction of the Semail ophiolite resulted in south-westward thrusting of the accreted slope (Sumeini complex) and deep-marine Hawasina thrust sheets over the Arabian margin (Callot et al, 2017;Tarapoanca et al, 2013).…”
Section: Albian-cenomanian To Turonianmentioning
confidence: 99%
“…The Semail ophiolite was obducted onto the northeastern margin of the Arabian plate, along with the allochthonous thrust sheets beneath (Coleman, 1981;Glennie et al, 1973Glennie et al, , 1974Searle, 2007). The initial oceanic subduction of Tethyan oceanic crust below the Semail ophiolite occurred at about 96-95 Ma from U-Pb zircon dating of metamorphic sole amphibolites accreted along the base of ophiolite (Rioux et al, 2016) and the ensuing continental margin subduction reached its peak high-pressure metamorphism at about 81-77 Ma (Garber et al, 2021;Warren et al, 2003). The obduction of the Semail ophiolite resulted in south-westward thrusting of the accreted slope (Sumeini complex) and deep-marine Hawasina thrust sheets over the Arabian margin (Callot et al, 2017;Tarapoanca et al, 2013).…”
Section: Albian-cenomanian To Turonianmentioning
confidence: 99%
“…Leng and Gurnis (2011) proposed that slab sinking causes a strong influx of asthenosphere above the foundering slab (Figure 6d). This rollback must have followed initial melting of the sole by 100 Ma (Garber et al, 2021) and subsequently caused fast spreading forming the Samail Ophiolite at 96-94 Ma. Rollback probably aided the clockwise rotation of the Samail subduction zone as indicated by paleomagnetic data (Morris et al, 2016;van Hinsbergen et al, 2019).…”
Section: Subduction and Obductionmentioning
confidence: 99%
“…The As Sifah Unit experienced HP metamorphism at 78 ± 2 Ma (El-Shazly et al, 2001) or 79 ± 1 Ma (Warren et al, 2003(Warren et al, , 2005 (see detailed discussion in Hansman et al (2021)). Garber et al (2021) reported three Sm-Nd garnet-whole-rock ages between 81 ± 1 and 78 ± 2 Ma. Because the garnets have typical growth zonation, the latter ages reflect a prograde-to-peak HP stage.…”
Section: Saih Hatat Windowmentioning
confidence: 99%
See 1 more Smart Citation
“…And finally, studies of the Samail ophiolite have been greatly enriched by ongoing research on the processes of ophiolite emplacement, and related deformation within and surrounding ophiolites. We are delighted that seven papers in this Special Issue address these new data (Cox et al., 2021; A. D. Evans et al., 2021; Garber et al., 2021; Ninkabou et al., 2021; Pilia et al., 2021; Rioux, Benoit, et al., 2021; Rioux, Garber, et al., 2021), though of course much recent work on this topic has also been published elsewhere.…”
Section: Introductionmentioning
confidence: 97%